Power, Privilege and Knowledge: the Untenable Promise of Co-production in Mental “Health” - Rose, Diana; Kalathil, Jayasree (Frontiers in Sociology, 2019)
This paper examines the concept and practice of coproduction in mental health. By analyzing personal experience as well as the historical antecedents of coproduction, we argue that the site of coproduction is defined by the legacy of the Enlightenment and its notions of “reason” and “the cognitive subject.” We show the enduring impact of these notions in producing and perpetuating the power dynamics between professionals, researchers, policy makers and service users within privileged sites of knowledge production, whereby those deemed to lack reason—the mad and the racialized mad in particular—and their knowledge are radically inferiorised. Articulating problems in what is considered knowledge and methods of knowing, we argue that modern “psy” sciences instantiates the privilege of reason as well as of whiteness. We then examine how the survivor movement, and the emergent survivor/mad knowledge base, duplicates white privilege even as it interrogates privileges of reason and cognition. Describing how we grapple with these issues in an ongoing project—EURIKHA—which aims to map the knowledge produced by service users, survivors and persons with psychosocial disabilities globally, we offer some suggestions. Coproduction between researchers, policy makers and those of us positioned as mad, particularly as mad people of color, we argue, cannot happen in knowledge production environments continuing to operate within assumptions and philosophies that privilege reason as well as white, Eurocentric thinking. We seek not to coproduce but to challenge and change thinking and support for psychosocial suffering in contexts local to people's lives.